Influence of synthesis temperature and atmosphere on Te4+ ion formation in lithium tellurite glass - Capiotto, Adriana do Carmo (2021)
In this research, the influence of synthesis process under Te4+ ion formation in lithium tellurite glass was investigated based in their optical and structural characteristics. The same 80TeO2 + 20Li2O nominal composition (in mol%) was used to prepare glasses with different synthesis temperatures (Ts = 600, 700, 750, 800 and 850 °C) and atmospheres (room, oxygen and argon). The study was based in the investigation of the UV–Vis absorption spectroscopy, Raman spectroscopy, photoluminescence (PL) and photoluminescence excitation (PLE) spectroscopies. The linear refractive index was measured in function of the wavelength ranging all the visible region. The results indicate that Te4+ concentration into the glass is strongly dependent on both synthesis temperature and atmosphere. A more intense emission is observed in glasses prepared in oxygen atmosphere and in the 750–800 °C temperature range.